Associations of functional and biochemical parameters of endothelial dysfunction in postmenopausal women with a different state of carbohydrate metabolism - Lyudmila Aleksandrovna Ruyatkina (Endocrinology Research Centre, 2015)
Most of the questions regarding vascular and rheological regulation related to normal health and disorders of carbohydrate metabolism remain unclear, which is important in the pathogenesis of angiopathy. Consequently, in the literature, there is no information about the function of endothelial vasomotion during occlusion. The present study investigated early postmenopausal women, when clinical, metabolic, and hemodynamic disturbances often manifest.Aim. To study the association between clinical and biochemical indicators of endothelial microcirculation in naturally postmenopausal women with different carbohydrate metabolism statuses.Materials and methods. We surveyed 94 postmenopausal women who were divided into three groups based on their carbohydrate metabolism status: group 1, type 2 diabetes mellitus (n = 52); group 2, prediabetes (n = 16); group 3, normoglycemia (n = 26). The following indicators were assessed: lipid profiles and anthropometric fasting plasma glucose, glycated hemoglobin, vascular endothelial growth factor (VEGF), and endothelin-1 levels. Microcirculation was evaluated by laser Doppler flowmetry (LDF). Statistical analysis was performed using SPSS software (version 17.0).Results. LDF parameters in group 3 were significantly different from group 1 during occlusion and reperfusion and also from group 2 in basal blood flow. During occlusion, the frequency of microcirculation oscillation was higher in group 1, whereas the amplitude of oxygen saturation oscillation was lower in group 3 than those in group 2. VraEr and Vra/mEr indicators during reperfusion in group 1 and VrfEf during basal blood flow in group 2 were higher than those in group 3; Vr parameters reflect the contribution of fluctuations in the relative erythrocyte volume in the probed area of skin to the modulation of vascular tone. In group 1, occlusal LDF indicators correlated with waist circumference, whereas VEGF, lipid profile parameters, and reperfusion parameters, VraEr correlated with systolic blood pressure and lipid profile. In group 2, VrfEf inversely correlated with VEGF levels, and in group 3, the frequency of microcirculation oscillation inversely correlated with endothelin-1 levels.Conclusions. We revealed the associations of metabolic, anthropometric, and hemodynamic factors as well as biochemical markers of endothelial dysfunction with microcirculation parameters in various modes of endothelial activity (basal, occlusion, and reperfusion) in postmenopausal women according to their carbohydrate metabolism status; we also describe the effect of age on microvasculature vasomotion.